The influence of perceived creativity and positive emotions on relationship quality: The mediating role of interaction - Burhanudin Burhanudin; Shinta Nufus Aulia (Universitas Ahmad Dahlan, 2023)
Online grocery shopping offers a convenient shopping experience, but service providers must be creative in meeting customers' needs and delivering a positive shopping experience. This research examines the influence of perceived creativity and positive emotions on interaction and, subsequently, relationship quality. The study also analyses the mediation role of interaction in the relationship between perceived creativity and connection quality and the relationship between positive emotions and relationship quality. A survey was conducted with 288 respondents to investigate the relationships among the variables. The data collected were analyzed using structural equation modelling. The results show that perceived creativity and positive emotions directly influence relationship quality. Furthermore, perceived imagination and positive emotions indirectly affect relationship quality through interaction. These findings suggest that online grocery shopping platform providers can leverage consumers' creative perceptions and positive emotions to create exchanges that can be used to build a quality relationship between service providers and consumers.